A Study on the Propagation of Cracks in A Reinforced Concrete Beam Incorporating Spent Garnet Subjected to Repeated Impact Loads - Basirun, Maizatul Najihah; Mokhatar, Shahrul Niza (Recent Trends in Civil Engineering and Built Environment, 2026)
In recent decades, global development has significantly impacted the environment due to the escalating demand for natural sand, a crucial component in concrete production. The exploitation of non-renewable sand resources through mining raises concerns about erosion, negatively affecting ecosystems, and altering hydrogeological and hydrological systems. The use of garnet from surface cleaning processes in the shipping industry, often discarded as waste, contributes to pollution. To address sustainability concerns, this study explores the use of spent garnet as a replacement for sand in concrete production. Concrete cubes with a size of 100×100 mm varying in spent garnet content 0%, 10%, 20%, 30%, and 40% exhibit optimal strength at a 40% replacement level, as demonstrated by compressive strength tests at 7 and 28 days. Repeated impact load using a 100 kg impact weight dropped with a height of 1.5 m on beam specimens measuring 120× 150×800 mm with a velocity of 5.4 m/s reveal that the resulting crack pattern is influenced by the amount of garnet used, with fewer flexural and shear cracks observed at the 40% spent garnet level. In conclusion, the utilization of spent garnet has the potential to be a sustainable material, offering an alternative to reduce reliance on natural sand in concrete mixes.